Analysis of Decreased Limestone Production on the Effect of Rainfall with the Linear Regression Method - Muhammad Tri Aditya; Helik Susilo; Yazid Fanani (Westscience Press, 2023)
Limestone mining is a quarry system mining . Its production is influenced by weather factors, especially rainfall. This study aimed at determining the mathematical model wich is able to correlate the influence of rainfall on production of limestone. In addition, it analyzed the correlation between rainfall and limestone production using linear regression method. There are four important steps in this research. The first step is to collect data production and production factors. The second step is to process the data into a mathematical model using linear regression. The third step is to test the result of the mathematical model with the statistical test method. Then the fourth step is to analyze the mathematical model that has met the statistical test results. The results showed that the best mathematical model was: Log P = 0.502 x LOG((JO X Pr) 1.99 x (CH)-0.001) + 0.0002. In conclusion, the effect of rainfall toward the production derivation was very low. Besides, operation hours and productivity also affected production derivation.